ANALISIS PERUBAHAN LAJU ALIR DAN POTENSI SUMUR DENGAN MENGGUNAKAN METODE MASS BALANCE DAN WEIR BOX UNTUK MENENTUKAN BESARNYA DAYA LISTRIK YANG DIHASILKAN - Martasari, Rial Dwi; Tornando, Trendy; Indarti, Adrian (CV. Ridwan Publisher, 2019)
This research is done in PT Geo Dipa Energi Dieng, Banjarnegara Regency, Central Java Province. The consideration is PT Geo Dipa Energi Dieng is one geothermal power plant in Indonesia which has the characteristics of reservoir double phase with water dominated, so interesting to be the place of the research because the equipment production is complex. The method of calculation in this research by using Mass Balance and Weir Box method which is used to calculate the flow rate of geothermal fluid production, the potential of wells and the amount of power electricity generated. Geothermal flow fluid flow rate calculation is very important and must be done at any time, since the production of geothermal wells must be tailored to the needs, the production equipment and the power plant equipment which can be arranged by using the wellhead. Based on Mass Balance and Weir Box Method, the calculation of vapor and brine mass flow rate from January 1, 2017 to February 22, 2017 obtained the average value of vapor mass flow rate (MVapour) is 29.4785 tons / hour, water flow rate of mass (MBrine) is 44.31 tons / hour, total fluid mass flow rate (MTotal) is 73.782 tons / hour, vapor fraction is 39.94688%, brass fraction is 60.05312%, flowing enthalpy is 1620 kJ / kg, potential The total well (gross) is 33.205 MW. The net potential is 13.2653 MW, resulting in 3.93 MWe of electricity. Keywords: Flow Rate, Electricity, Mass Balance, Potential Well And Weir Box